SISTEM MONITORING IRIGASI DI LAHAN SAWAH BERBASIS LoRa (Long Range) - Fian, Aris Okta (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH, 2021)
Agriculture is one of the fields that is very important to meet basic human needs. When these basic needs are not sufficient, it will be a threat to human survival. One of the biggest problems in agriculture is the lack of water and not necessarily the irrigation system. So from the problems above, the author wants to create a tool for monitoring irrigation irrigation based on LoRa (Long Range), LoRa (Long Range) itself is a unique and amazing modulation format created by Semtech. This tool serves as an assistant or replaces the task of farmers to carry out irrigation automatically according to the water needs for the fields. So as to make the water needs in the fields will be fulfilled optimally, effectively and efficiently.